(untitled) (Journal of Health Sciences, 2023)
Introduction: Pleural complications in coronavirus disease 2019 (COVID-19) are relatively uncommon findings. Pleural involvement in these patients may directly correlate to disease severity and overall prognosis. We aimed to review clinical features and treatment approaches for pleural complications (accumulation of fluid/air inside the pleural cavity) in 45 patients with COVID-19, who were treated at our institution between April 2020 and October 2021. Methods: Our study was designed as single-center, observational, cross-sectional study of 45 patients with COVID-19 and at least one radiologically verified pleural complication. Demographic data, radiological findings, as well as type and number of thoracosurgical intervention(s) were recorded for every patient. We included patients of both genders and various age groups, with positive RT-PCR assay for COVID-19 and radiologic features of pleural complications, which required single or multiple thoracosurgical interventions. Results: Unilateral pleural complications were more common, right-sided pleural complications were found in 44.4% of patients. Right-sided pneumothorax was reported in 26.7% of patients. Almost one-fourth of our patients required invasive mechanical ventilation. Tube thoracostomy was performed in 84.4% of patients with unilateral pleural complications. A fatal outcome was most common in patients over 60 years old. More than half of patients with bilateral pleural complications died in our study. Conclusions: Pleural complications are a rare finding in patients with COVID-19. Tube thoracostomy is the mainstay of treatment for most symptomatic patients with pleural complications. Future research should be directed toward investigation of long-term pulmonary consequences in patients with COVID-19.